Educational Environment in A Medical College: Exploration of Strengths, Weaknesses and Improvement Strategies - Hassan, Mahmood Ul; Ashar, Abid (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess the Dundee Ready Education Environment Measure (DREEM) score of the college environment with identification of strengths and weaknesses and suggesting remedial measures.Study Design: Mixed method sequential explanatory study.Place and Duration of Study: Peshawar Medical College, Peshawar Pakistan, from Feb to Apr 2019.Methodology: Dundee Ready Education Environment Measure (DREEM) questionnaire was used to quantitatively assess the educational environment of the college while in the qualitative part of the study, interviews were conducted to find out remedial measures to overcome the weaknesses and to further improve identified strengths.Results: In the quantitative part of the study, the overall DREEM score of the college was calculated to be 130.576. Taken separately, 1st year, 3rd year and final years had scores of 128.38, 131.97 and 131.40 respectively, which were rated as more positive than negative. This study identified that students feel overburdened with studies and feel stressed. In the qualitative part of the study, thematic analysis of interviews identified that stress and time management workshops at regular intervals, establishing student support groups, strengthening mentorship programs, frequent formative assessment and involvement of students in the curricular forums are possible remedial measures.Conclusion: Oue student’s perception of college educational environment is positive. Overburdening with studies and stress in medical students were identified as problem areas. Identified improvement measures included establishing support groups for the students, arranging stress management workshops and strengthening mentorship programs.